DEVELOPMENT OF TRANS-EUROPEAN SUTURE ZONE IN POLAND: FROM EDIACARAN RIFTING TO EARLY PALAEOZOIC ACCRETION - Nawrocki J.; Poprawa P. (My University, 2006)
This contribution summarizes selected results of the "Palaeozoic Accretion of Poland" Project. Emphasis is placed on geochronological, geochemical and palaeomagnetic constraints on the Late Neoproterozoic to Early Palaeozoic development of the Trans-European Suture Zone (TESZ). During the Late Neoproterozoic break-up of Rodinia, a major rift developed in the area of the future TESZ along which Baltica was separated from peri-Gondwana and Laurentia, resulting in opening of the Tornquist Ocean and development of the southwestern Baltica passive margin. This was paralleled by the development of the Cadomian orogenic system along the margin of Gondwana and the eastern and southern margins of Baltica. Some tectonic units involved in the TESZ, such as the Brunovistulian Terrane and the Małopolska Massif characterized by Cadomian basement, were derived from the internal and external parts of the Cadomian Orogen, presumably somewhere at the SE or SW comers of Baltica. Determination of areas where these terrains were originally located depends strongly on the Ediacaran plate model that is adopted for Baltica. The Małopolska Massif was re-accreted to Baltica, presumably due to latest Ediacaran strike-slip tectonics, during the late Middle to Late Cambrian, causing at that time an interruption of its passive margin subsidence pattern and minor erosion. During Late Ordovician to Silurian times, the Caledonian collision of Gondwana-derived East Avalonia Terrane with Baltica gave rise to the development of a foredeep basin along the southwestern margin of Baltica. The proximal part of this foredeep corresponds to the Pomeranian region to the Koszalin-Chojnice Zone, and its distal parts to the Baltic Basin, both of which developed on Baltica basement. During Ordovician and Silurian times clastics were shed into the Koszalin-Chojnice Zone and the Baltic Basin from the evolving Caledonian orogenic wedge, consisting of a subduction-related volcanic arc, obducted ophiolites and accretionary prism, as well as crustal units that were detached from basement of Baltica and Avalonia. The Brunovistulian Terrane was accreted to the Małopolska Massif at the turn from the Silurian to the Devonian, Proximal terranes, such as the Pomerania and Łysogóry units remained after Late Neoproterozoic rifting in a position close to the relatively mobile SW margins of Baltica.
Keywords: ACCRETION; EARLY PALAEOZOIC; EDIACARAN; RIFTING; TERRANE; TRANS-EUROPEAN SUTURE ZONE; Precambrian::Proterozoic::Neoproterozoic::Ediacaran; Докембрий::Протерозой::Неопротерозойская::Эдиакарий